HUBUNGAN PENGETAHUAN SIKAP DAN PERILAKU TENTANG NYERI PADA LANSIA DI POSYANDU LANSIA KUSUMA DESA PALUR MOJOLABAN SUKOHARJO - RIYANTO , DIDIK (2010)

(untitled)
Increasingly expectation of life to someone, its mean more account of elderly. Elderly had Many problems of health is like physical and mentality. Healthy problem who is ever attack to elderly is paint , but until now, many elderly still know yet how should be done if they were sick of paint. Unknown at the elderly by paint causing some factors, namely knowledge and attitude. knowledge and attitude by elderly will influence toward behavior about elderly paint. The objective of this research is aim to know relation the relation among knowledge, attitude and behavior about elderly paint in Kusuma Posyandu at Palur Village Mojolaban of Sukoharjo responders are all of population who noted as member of Kusuma Posyandu elderly with 67 persons. Sampling method is total sampling. Statistical test is using Chi Square test. Statistical test had result: knowledge level of responder is height, counted 50,3%, attitude of responders are positive counted 79,1%, behavior about elderly paint is good counted 71,6%. The conclusion is the relation between knowledge and behavior about elderly paint in Kusuma Posyandu at Palur village Mojolaban of Sukoharjo. There is relation between attitude and behavior about elderly paint in Kusuma Posyandu at Palur village Mojolaban of Sukoharjo.